The Role of Judges in Realizing the Three Basic Legal Values Reviewed from Gustav Radbruch's View - KRISTHY, Mutia Evi; HAMDANI, Helmi; SIAMIKO, Miko; SANJAYA, Oki (Journal of Political And Legal Sovereignty, 2023)
Purpose - Judicial power is necessary in a legal state. Judicial power functions to enforce the law by force. Forced law enforcement aims to achieve legal objectives. According to Gustav Radbruch, the law aims to fulfill a sense of justice, certainty, and benefit in living together.AMethodology - The fundamental values of law which, according to Gustav Radbruch, include justice (philosophical), legal certainty (juridical), and benefits for society (sociological)Findings - Gustav Radbruch's view of the three primary legal values is very important for judges in deciding cases. In realizing these values, judges should remain neutral, independent, and free and not be interfered with by political or government interests.Implication - Officials implementing judicial power should uphold the philosophical, juridical, theological, and moral meaning of irah-irah "for the sake of justice based on belief in the Almighty God" in every decision they pronounce. Conflicts in upholding justice, expediency, and legal certainty should not make every law and decision useless for a society that believes in justice.